The role of microcredit in promoting self-employment in urban area : Lesson from Amanah Ikhtiar Malaysia (AIM), Malaysia / Siti Noor Shamilah Misnan...[et al.] - Misnan, Siti Noor Shamilah; Mohd Noor, Rafizah; Ramli, Rosfaraliza Azura (Universiti Teknologi MARA, Kedah, 2019)
Some scholars’ view of microcredit’s potential as a tool of enhances the quality of life and poverty alleviation. Microcredit scheme create opportunities for participants to get involved in the self-employment and involved in the entrepreneurship programme. It seem that this scheme create an opportunities for the participants to be independent in creating self-economic. In the case of Malaysia, AIM’s microcredits program is a group-based lending and become a platform to produce entrepreneur as well as antipoverty intervention and increasing the quality of life and social empowerment. Traditionally, microcredit aims to break the rural poor in developing countries especially groups of unable to access bank loans and poor villagers rely on local moneylenders. For this situation, microcredit provides an alternative source of credit and offering collateral-free loans. Currently, there are debates of urban poverty and role of microcredit to empower this group. Previous studies showed that microcredit has changed the socio-economic of the participant in increasing empowerment, entrepreneur skills, transformational thinking and a desire to improve get out from poverty. Thus, this conceptual paper will study and discuss the mechanism of promoting self-employment in urban area. Following discussion of this concept paper of microcredit is expected to give implication to policy maker, agencies that offers micro credit, as well as for the community in general. .